Characterization of the Phosphofructokinase Gene Family in Rice and Its Expression Under Oxygen Deficiency Stress - Mustroph, Angelika; Stock, Johanna; Hess, Natalia; Aldous, Sophia; Dreilich, Anika; Grimm, Bernhard (Frontiers in Plant Science, 2013)
Plants possess two types of phosphofructokinase proteins for phosphorylation of fructose-6-phosphate, the ATP-dependent phosphofructokinase (PFK) and the pyrophosphate-(PPi) dependent pyrophosphate-fructose-6-phosphate-phosphotransferase (PFP). During oxygen deficiency ATP levels in rice seedlings are severely reduced, and it is hypothesized that PPi is used as an alternative energy source for the phosphorylation of fructose-6-phosphate during glycolysis. In this study, we analyzed the expression of 15 phosphofructokinase-encoding genes in roots and aerial tissues of anoxia-tolerant rice seedlings in response to anoxic stress and compared our data with transcript profiles obtained from microarray analyses. Furthermore, the intracellular localization of rice PFK proteins was determined, and the PFK and PFP isoforms were grouped in a phylogenetic tree. Two PFK and two PFP transcripts accumulated during anoxic stress, whereas mRNA levels of four PFK and three PFP genes were decreased. The total specific activity of both PFK and PFP changed only slightly during a 24 h anoxia treatment. It is assumed that expression of different isoforms and their catalytic properties differ during normoxic and anoxic conditions and contribute to balanced glycolytic activity during the low oxygen stress. These characterizations of phosphofructokinase genes and the comparison to other plant species allowed us to suggest candidate rice genes for adaptation to anoxic stress.